"Doubly Mother": Heterologous Artificial Insemination Between Biological and Social Parenthood: A Single Case Study. Issue 7 (3rd October 2019) - Tamanza, Giancarlo; Facchin, Federica; Francini, Federica; Ravani, Silvia; Gennari, Marialuisa; Mannino, Giuseppe
Abstract : In heterologous artificial insemination, the donation of gametes (either sperm or eggs) from a third person allows infertile and same-sex couples to become parents. Therefore, the child is genetically related to one parent, while the other parent is referred to as the social mother or father. This current single case study aimed at investigating this double access to parenthood in a lesbian couple who had two children after heterologous artificial insemination. In this couple, both women delivered one of the two children, so that each partner is either biological or social mother. The Clinical Generational Interview was used to assess the quality of family relationships, with a specific focus on three dimensions: the origins of each partner, the constitution of the couple, and the generational passage. Paper and pencil textual analysis was conducted following the principles of Interpretative Phenomenological Analysis and led to the identification of six dominant themes (and subthemes): (a) relationship with the family of origin ; (b) couple relationship ; (c) generational passage ; (d) heterologous artificial insemination and "double motherhood" ; (e) donor/biological father ; and (f) children identity and the disclosure of their origin . This study's findings revealed the importance of using research techniques aimed at in-depth exploration of this phenomenon consistently with the specificities of the new filiation forms. The adoption of a transgenerational perspective allows articulating conception coordinates with the history of the couple and each partner's origins.